Analisis Potensi Dan Strategi Pengembangan Pariwisata di Kabupaten Ende - Yustina Paulina Penu (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
This research aims to make an inventory of the potential and strategies for developing tourism in Ende Regency as a tourist attraction, so that policies can be used to develop this attraction in a sustainable manner. This research was conducted in Ende district. Data collection in this study was carried out using the following techniques: 1)) Direct interviews with respondents by visiting respondents based on a questionnaire (list of questions) that had been prepared previously. 2) Observation, which is a collection of data by direct observation in the field to test and complete other data. 3) Documentation, namely obtaining data and information that has been recorded in various documents about various things needed in research that can be obtained from related agencies, such as the Tourism Office, TNK, Inns, Home Stay, Regional Libraries. The problems in this study were analyzed descriptively qualitatively, IFAS analysis (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) and SWOT analysis (Strength Weakneses Opportunities Threat) analysis to design development strategies. From the research results, it was found that the internal conditions in the form of strength factors in each tourism area in Ende Regency were beautiful natural panoramas, unique community cultures, historical relics, unique social life, beautiful forests with fresh air. Internal conditions are in the form of weakness factors, including: lack of facilities and infrastructure to support tourism activities, lack of promotion of tourism potentials in each area, lack of human resources in the tourism sector, lack of air, sea and air transportation accessibility and the road to tourism potentials is still narrow, there is a lack of local community involvement in tourism activities in their place. The results of the IFAS matrix analysis found that the internal condition of tourism potential in Ende district was in a moderate position, with a total score of 2.33. External conditions in the form of opportunity factors in each area include: The existence of the mission of Ende district 2014-2019, the proximity of tourism potential in areas other than Kelimutu to the tourist attraction of Kelimutu National Park, strategic location and in the middle route of Ende Regency and Flores Island, advances in information technology and transportation, a trend towards world tourism towards natural tourism (Back to Nature), the growth of the global economy. External conditions in the form of threat factors are the threat of global warming, the circulation of drugs, HIV, the threat of population growth due to migrants resulting in land conversion, cultural change (commodification) and environmental pollution in the form of garbage. The results of the EFAS matrix analysis show the position of the external environment. The tourism potential of Ende Regency as a tourist attraction is in a moderate position, with a total score of 2.44. The general strategy used in developing tourism potential in each area is a strategy of maintaining and maintaining. This position states that the tourism potential in each tourism area has an average moderate and competitive attractiveness position. Alternative strategies for developing tourism potential, including: tourism product development strategies in each region, infrastructure and facilities development strategies, tourism product marketing strategies, institutional development strategies and human resource enhancement in tourism, and sustainable tourism development strategies.